"Hemophagocytic Lymphohistiocytosis after EBV reactivation and ibrutinib treatment in relapsed/refractory Chronic Lymphocytic Leukemia". (2017) - Cavallari, Maurizio; Ciccone, Maria; Falzoni, Simonetta; Cavazzini, Francesco; Formigaro, Luca; Di Virgilio, Francesco; Rotola, Antonella; Rigolin, Gian Matteo; Cuneo, Antonio
Abstract: Hemophagocytic Lymphohistiocytosis (HLH) is a rare syndrome characterized by ineffective T-cell and NK response. We report the clinical course of a patient with relapsed CLL who developed acute symptoms soon after starting ibrutinib. Hyperpyrexia, splenomegaly, hyperferritinemia, hypertriglyceridemia, cytopenias, and a typical cytokine pattern, i.e. high interleukin (IL)−6, IL10 and IL18, were consistent with a diagnosis of HLH. Coexistent Epstein Barr virus reactivation was documented. Ibrutinib-induced impairment of NK degranulation, associated with EBV reactivation and CLL-related immunodeficiency may have contributed to the development of HLH in our patient. Highlights: This is the first report describing a case of well-documented HLH in relapsed CLL under ibrutinib. There was a strict temporal association between ibrutinib start and HLH. The patient had concomitant EBV reactivation, a known possible trigger of HLH. The effect of ibrutinib on NK and T-cell was a possible contributing factor to the onset of HLH.